The Role of Innovation in Improving the Competitiveness of UMKM in the Digital Era - Gultom, Petra Aprianti; Sitanggang, Lestari Pratiwi; Sinurat, Indriyani; Trisanti, Ayu; Br. Tarigan, Miska Irani (Sean Institute, 2025)
The purpose of this literature review is to comprehensively examine how innovation plays a role in increasing the competitiveness of Micro, Small, and Medium Enterprises (UMKM) in the current digital era. This study uses a qualitative research method with a literature review approach to various relevant previous research results for the 2020–2025 period. The literature sources used include scientific journals discussing product innovation, service innovation, digitalization, and digital marketing strategies applied to UMKM. The results show that innovation is a key component that helps UMKM become more competitive by creating innovative products, improving the quality of technology-based services, and implementing effective digital marketing strategies. These three aspects of innovation have been proven to strengthen the position of UMKM in facing changes and increasingly competitive global business.